2007
DOI: 10.1128/aac.01618-06
|View full text |Cite
|
Sign up to set email alerts
|

Universal In Vitro Antifungal Resistance of Genetic Clades of the Fusarium solani Species Complex

Abstract: Eleven antifungal drugs were tested against representative isolates of the four phylogenetic clades of the Fusarium solani species complex obtained in a multilocus sequence analysis. They all showed very poor activity, with no differences among the clades. Amphotericin B was the most active drug.Fusarium solani is a fungus that is widely distributed in nature and is able to produce many plant diseases with important economic impacts and, also, severe, usually fatal, human infections (7,9,15,23). These infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
85
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 28 publications
13
85
0
5
Order By: Relevance
“…Species-specific differences in the susceptibility of Fusarium isolates was apparent in the MICs to amphotericin B, voriconazole, and posaconazole. In agreement with previous reports [16,37], amphotericin B was the most effective agent across all isolates. The European Society of Clinical Microbiology and Infectious Diseases (ESCMID) and the European Confederation of Medical Mycology (ECMM) recommend amphotericin B and voriconazole as the first optional agents in the treatment of cases with fusariosis [18].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Species-specific differences in the susceptibility of Fusarium isolates was apparent in the MICs to amphotericin B, voriconazole, and posaconazole. In agreement with previous reports [16,37], amphotericin B was the most effective agent across all isolates. The European Society of Clinical Microbiology and Infectious Diseases (ESCMID) and the European Confederation of Medical Mycology (ECMM) recommend amphotericin B and voriconazole as the first optional agents in the treatment of cases with fusariosis [18].…”
Section: Discussionsupporting
confidence: 81%
“…However, in the present study, these compounds were not effective against some of the species, sometimes indicating high degrees of intraspecific variability (Table 4). Some studies have reported that the MIC values in F. verticillioides were high for amphotericin B and low for posaconazole [16,37]. Similarly, we also observed activity of posaconazole against this species, but with a limited degree of confidence.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…In humans, they cause infections ranging from superficial disease (e.g., keratitis and onychomycosis) to life-threatening disseminated infections; the latter occur predominantly in severely immunocompromised patients (7,18,19) in whom mortality approaches 100% (10). This high mortality is due in part to frequent delays in diagnosis and to the fact that most Fusarium species, particularly those nested within the Fusarium solani species complex (FSSC), are typically resistant to most antifungal agents (1,2,28).…”
mentioning
confidence: 99%